Outcome after high-dose chemotherapy and autologous stem cell transplantation in patients with aggressive B-cell non-Hodgkin's lymphoma - Kriegsmann, Katharina; Rieger, Michael; Schwarzbich, Mark-Alexander; Sitter, Sören; Kriegsmann, Mark; Bruckner, Thomas; Hensel, Manfred; Ho, Anthony Dick; Witzens-Harig, Mathias; Wuchter, Patrick (European journal of haematology, 2018)
Objective For more than two decades, high-dose chemotherapy (HDT) and autologous blood stem cell transplantation (ABSCT) were treatment options for patients with aggressive B-cell non-Hodgkin's lymphoma (B-NHL). However, the ideal timing and the collective patient benefits are still being debated. Method We retrospectively analyzed the data of 163 patients with B-NHL who received an HDT protocol followed by ABSCT between 2001 and 2007. Patients were analyzed according to the time point of HDT/ABSCT to compare upfront (directly after induction, n = 72, 44%) versus secondary transplantation (at first relapse, n = 91, 56%). Results The overall response rate was 100% and 94% after upfront and secondary HDT/ABSCT, respectively. No significant differences were found for hematopoietic recovery and toxicity profile. The progression-free survival (PFS) and overall survival (OS) probability were found to be significantly higher in the upfront HDT/ABSCT treatment group (P = .018 and P = .004). In multivariate analysis, upfront HDT/ABSCT and low IPI risk score had a significant beneficial effect on OS (P = .031 and P = .019). Conclusion HDT and ABSCT directly after induction chemotherapy were confirmed to be feasible with high PFS and OS rates. In addition, for patients with relapse after first-line therapy and consecutively poor prognosis, HDT/ABSCT also offers an effective treatment strategy.